Proportion of fish catches types and fishing changes of purse seine in Spermonde water in East season on 2015 and 2019. Issue 1 (September 2020) - Nelwan, A F P; Musbir; Kurnia, M; Palo; Jaya, I
Abstract: The proportion of fish type is the percentage of each fish caught. The chances of catching are the percentage of fish types caught from the number of days fishing operations. The purpose of this research is Komposisiand 2019 in Spermonde. Data collection location in Sanane Island and Badi Island, Pangkep regency. This study was a case study on purse seine, where data retrieval was conducted in May until July 2015 and July until August 2019. The number of days of fishing operation on 30 fishing trip. The results showed that there were nine types of fish that had been caught from the Purse Seine in 2015. In 2019 there are 11 types of fish that are caught on the purse seine. In the year 2015, the dominant caught is tembang ( Sardinella fimbriata ) on the first and second hauling. In the year 2019, the dominant caught is the type of selar ( selaroides leptolepis ), on the first and second hauling. The highest percentage of fishing chance in the year 2015, is the type of Tembang fish on the first and second hauling. Likewise, in 2019 the biggest catching chance is a type of selar fish, both on the first and second hauling. The activity of a purse seine in the east season in the waters of Spermonde indicates that there is a difference in the composition of types of fish fishing. Likewise, the fishing chance are in the years 2015 and 2019.